Check list and zoogeographic analysis of the scale insect fauna (Hemiptera: Coccomorpha) of Greece - Pellizzari, Giuseppina; Chadzidimitriou, Evangelia; Milonas, Panagiotis; Stathas, George J.; Kozár, Ferenc (Zootaxa, 2015)
This paper presents an updated checklist of the Greek scale insect fauna and the results of the first zoogeographic analysis of the Greek scale insect fauna. According to the latest data, the scale insect fauna of the whole Greek territory includes 207 species; of which 187 species are recorded from mainland Greece and the minor islands, whereas only 87 species are known from Crete. The most rich families are the Diaspididae (with 86 species), followed by Coccidae (with 35 species) and Pseudococcidae (with 34 species). In this study the results of a zoogeographic analysis of scale insect fauna from mainland Greece and Crete are also presented. Five species, four from mainland Greece and one from Crete are considered to be endemic. Comparison with the scale insect fauna of other countries is provided.